Artificial Intelligence and Climate Change: Response to Climate-Induced Disasters in Pakistan - Jugnoo Aijaz; Adil Sultan (CISS Insight Journal, 2024)
Pakistan is grappling with the impacts of climate change, which have intensified the severity of disasters such as flash floods, glacial lake outbursts, droughts, and heat waves. These challenges pose serious threats to the country’s livelihoods and economy. One of the several ways to mitigate the impacts of climate change is by utilizing Artificial Intelligence (AI) for data gathering and analysis. This approach can help reduce the increasing frequency of major losses to life and property. However, several systemic challenges hinder progress, including inadequate infrastructure, the unavailability of required data and its proper representation, a lack of skilled manpower, endemic corruption, and a poor governance system. This paper analyzes the UN’s efforts to incorporate AI technology into climate mitigation and adaptation strategies, while examining various models employed by countries such as the United States, China, and Japan. The established practices of these countries could serve as a foundation for developing a Pakistan-specific model for flood risk management, disseminating disaster-related information, delivering early weather forecasts, and analyzing potential damage to infrastructure.